The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1590/s1516-05722009000100008
|View full text |Cite
|
Sign up to set email alerts
|

Variação no rendimento e composição química do óleo essencial de folhas de atroveran (Ocimum selloi Benth.) inteiras e moídas sob condições de armazenamento

Abstract: RESUMO:Além das características genéticas e ambientais, o sistema de cultivo e processamento das plantas medicinais também são fatores importantes para a determinação da qualidade final do produto. Entre estes está o armazenamento, sobre o qual há poucas informações a respeito da conservação de plantas medicinais. Este trabalho teve como objetivo estudar o efeito do tempo de armazenamento sobre o rendimento e a composição química do óleo essencial na biomassa seca de folhas inteiras e moídas de Ocimum selloi. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…The recommended packaging for storing leaves are: paper bags, polyethylene bags, cardboard boxes and paper bags type double kraft with an inner layer of non-toxic polyethylene [15]. Using polypropylene bags to store dry samples of whole and ground leaves of Ocimum selloi, and evaluating the effect of storage time on the yield and chemical composition of the essential oil of this plant, Costa et al [16] observed a marked reduction in the yield of essential oil both of the whole leaves and of the ground leaves during a year of storage. However, the yield obtained from whole leaves was significantly higher than that of the ground leaves.…”
Section: Researches That Evaluated Quality Attributes Of Medicinal Plants Stored Under Different Conditionsmentioning
confidence: 99%
“…The recommended packaging for storing leaves are: paper bags, polyethylene bags, cardboard boxes and paper bags type double kraft with an inner layer of non-toxic polyethylene [15]. Using polypropylene bags to store dry samples of whole and ground leaves of Ocimum selloi, and evaluating the effect of storage time on the yield and chemical composition of the essential oil of this plant, Costa et al [16] observed a marked reduction in the yield of essential oil both of the whole leaves and of the ground leaves during a year of storage. However, the yield obtained from whole leaves was significantly higher than that of the ground leaves.…”
Section: Researches That Evaluated Quality Attributes Of Medicinal Plants Stored Under Different Conditionsmentioning
confidence: 99%
“…The occurrence of three different chemotypes for O. selloi has been previously reported in literature [6][7][8][9] being one chemotype rich in methylchavicol, the second one rich in methyleugenol, and a third one, rich in methylchavicol and trans-anethole. For all plants analyzed in this study, methylchavicol was major compound found in their essential oils (Table 2).…”
mentioning
confidence: 99%
“…Due to the interesting results of these oils against C. albicans and the possibility to combine the odor of fresh mint of H. myrtoides with the anise odor of O. selloi in a future pharmaceutical formulation to treat oral candidiasis, we tested the combination of the two oils in order to verify the effect in their antimicrobial activity. The proportions tested aimed to spare the oil of H. myrtoides in respect to that of O. selloi, since H. myrtoides is native to regions of high altitudes, where it grows wild (making it hard to harvest), and the species O. selloi can be easily grown [5,9]. The proportions tested and the results obtained are shown in Table 4.…”
mentioning
confidence: 99%
“…Cada vez mais aumenta o interesse pelo estudo da caracterização e composição dos óleos essências de plantas para fins medicinais (POTZERNHEIM et al, 2006;MARCO et al, 2007;MAIA et al, 2007;VULPI et al, 2007;BORSATO et al, 2008;RODRIGUES et al, 2008;BOTREL et al, 2009;COSTA et al, 2009). …”
Section: Composição Do óLeo Essencial De Folhas De C Regiumunclassified